A case of mistaken (role) identity?: Envisioning entrepreneurial role demands. Issue 1 (2nd January 2021) - Krueger, Norris; Lawrence, Alexander
ABSTRACT: There has been a recent burst of interest in entrepreneurial role identity in various forms (triggered in large part of Fauchart & Gruber's landmark study in 2011). This essay addresses the evolution of entrepreneurial role identity, its possible pitfalls, and its growing potential. The authors also offer research suggestions centered on a most important issue in entrepreneurship: How have our training and education efforts changed how learners think at a deep level? How are we changing their mindset and ultimately their entrepreneurial potential?